Virtual laboratory and guided inquiry on students’ performance in redox reaction in Rivers State - Ndukwe, Uju Ethel; Obafemi, Deborah Temidayo Abiola (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
The study investigated the effect of the virtual laboratory and guided inquiry teaching strategies on students' performance in redox reactions in senior secondary schools in Obio/Akpor Local Government Area, Rivers State. The study adopted a quasi-experimental pre-test, post-test, and non-equivalent group design. Three research questions and three null hypotheses guided the study. A sample size of Eighty-five (85) SS2 students in their intact classes in three public senior secondary schools in Obio-Akpor Local Government Area were involved. A purposive sampling technique was used to select two public schools and one intact class from each school. A researcher-developed and validated instrument for data collection was the Chemistry Performance Test on Redox Reaction, with reliability coefficients of 0.88 obtained using the Kuder Richardson-21 (KR-21) formula. The mean and standard deviation were used to answer the questions, while the analysis of covariance (ANCOVA) was used to test the hypotheses at a 0.05 level of significance. The results obtained showed that guided inquiry enhanced the performance of students better than a virtual laboratory. There was a statistically significant difference between the effects of guided inquiry and virtual laboratories in favour of guided discovery. Furthermore, though the male students performed better than the female students, the difference in their performance was not significant. There is also no significant interaction between strategy and gender on students’ performance. The study recommended that chemistry teachers should be encouraged to use guided inquiry and virtual laboratory teaching strategies in teaching chemistry.